2001
DOI: 10.1080/10304310120059128
|View full text |Cite
|
Sign up to set email alerts
|

What Does John Gray Have to Say to Feminism?

Abstract: While the backlash therapy books may be written in feminist ink, they blot out the most basic precept of feminist therapy-that both social and personal growth are important, necessary and mutually reinforcing (Faludi, 1992, p. 373).Lately, I have had cause to go down to my local chain-bookstore in search of the odd feminist text. Interestingly, I have found these books rmly encased in the self-help section. Feminism's insistence on the personal being political means that it has been relegated to the shelf in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…According to liberal feminist literature (Tong 2009;Murdoch, 2001), men and entrepreneurship have always been synonymous in history and the characteristics of an entrepreneur such as risk taking, competition and growth orientation (Reuben, Sapienza, & Zingales, 2015;Fiske, Cuddy Glick et al, 2002) have leaned toward the masculine (Hechavarria & Ingram, 2016). On the other hand, women in the history of society have been associated with promoting and sustaining relationships on which humanity hinges (Singh & Islary, 2019; Kleinberg, 1990) hence the characteristics of bearing children, homemaking and nurturing the future generation have leaned toward the feminine (Ridgeway 2011).…”
Section: Theoretical and Contextual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…According to liberal feminist literature (Tong 2009;Murdoch, 2001), men and entrepreneurship have always been synonymous in history and the characteristics of an entrepreneur such as risk taking, competition and growth orientation (Reuben, Sapienza, & Zingales, 2015;Fiske, Cuddy Glick et al, 2002) have leaned toward the masculine (Hechavarria & Ingram, 2016). On the other hand, women in the history of society have been associated with promoting and sustaining relationships on which humanity hinges (Singh & Islary, 2019; Kleinberg, 1990) hence the characteristics of bearing children, homemaking and nurturing the future generation have leaned toward the feminine (Ridgeway 2011).…”
Section: Theoretical and Contextual Frameworkmentioning
confidence: 99%
“…Where husbands are not, women seek assistance and support from other networks closest to them. Husbands play a critical role in women's entrepreneurial success as they are the founders of the craft through patriarchy (Tong, 2009;Murdoch, 2001) and are the link through which women can be significantly empowered (Nikina, Shelton & LeLooarne, 2015). These findings concur with research done by Wolf and Frese (2018) that found a positive correlation between husbands' influence on the success of their wives' entrepreneurial ventures.…”
Section: Findings and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation